Actividades lúdicas y su impacto en la motricidad gruesa de los niños de educación inicial en la Unidad Educativa Francisco Huerta Rendón cantón Babahoyo - Sares Agurto, Angely Arleth (2023)
The present case study has as its research topic, play activities and their impact on the gross motor skills of children in early education at the "Francisco Huerta Rendón" Educational Unit, and its general objective is to analyse the play activities and their impact on the gross motor skills of children in early education at the "Francisco Huerta Rendón" Educational Unit in Babahoyo, The research was carried out using the descriptive method with a non-experimental design that allows us to evaluate certain characteristics of the population that is experiencing this problem and thus be able to have enough information to reach a conclusion. To collect the data, the survey was used as a technique and the questionnaire was applied as an instrument, which allowed us to know the opinion of the parents about the subject of the study. The results obtained through the research process are presented, among which we highlight the total approval of the respondents in the use of play activities, which will be a help for children in the development of their gross motor skills. Finally, the conclusions and recommendations are presented, which show the need to implement play activities in early education children, helping them in this way in the teaching-learning process, as well as acquiring new skills, abilities and knowledge appropriate to their age.